School Leadership Strategy to IncreaseTeacher Professionalism and Its Impact on the Quality of Learning Education at Marcelo 2 Comoro School - Isac Pinto de Jesus (PT. Anagata Sembagi Education, 2024)
Problem Formulation How are the school director's strategy steps to increase Professionalism Teacher in basic education. Research Objectives To analyses the School Director's strategy to increase Teacher Professionalism and its impact on improving the quality of basic education. The research findings will build theories for the School Leadership Strategy, especially increasing teacher professionalism, which focuses on the quality of learning. This knowledge will be a reference for the academic community and professionals to carry out continuous verification and discovery of this branch of science. In order to deepen our efforts, it is a basis to deepen and develop further for further research. Education is an inspiration for science, when the quality of the country's development process is in progress, the quality of basic education that is strong and strong can also affect the future development of the Nation. The leadership strategy has a range of ways to increase Professionalism teachers in order to have a good quality impact on learning for students. The method also has two or more meanings that are sought to find the practice of attitude, mentality, intellectual capacity, which has their purpose. The time for conducting the survey is on the start date and the end date. The start date of the survey was July 31th and August 11th 2023 and the location of the survey was conducted in the Basic. Education of Marcelo 2 Comoro Administrative Post of Dom Aleixo, Dili Municipality. Data collection techniques include Observation, Interview, documentation, data analysis techniques by qualitative methods, such as data collection, data reduction, data display, data verification. Research findings show that leadership responds to the same purpose that leaders aim to improve the quality of teaching learning through various ways to increase teacher professionalism to ensure quality of learning. In conclusion, the steps used by the leadership to improve the quality of the teacher's professionalism through a range of academic training, the leadership strategy is used to facilitate teachers at different levels of education to ensure quality, when implementing these strategies there are always obstacles but the leadership is low in order to overcome them, through leadership efforts it can contribute to improving the quality and quality of learning.